Selection and characterization of lactic acid bacteria with activity against Listeria monocytogenes from traditional RTE ripened foods. (15th June 2022) - Martín, Irene; Rodríguez, Alicia; Alía, Alberto; Martínez, Remigio; Córdoba, Juan J.
Abstract: Lactic-acid bacteria isolated throughout the ripening process from traditional RTE soft cheeses and dry-cured fermented sausages were characterized and selected for their anti- L. monocytogenes activity. For this, the LAB isolates were first screened for their activity against this pathogen in agar spot assay and further evaluated in cheese and dry-cured fermented sausage models simulating conditions of ripening of these products. From a total of 371 LAB isolates, 84 showed anti-listerial activity in agar spot assay and only 10 of them were selected for reducing L. monocytogenes counts in food models. The selected LAB strains belonged to the species Enterococcus faecium, Lacticaseibacillus casei, Lacticaseibacillus paracasei, Lactilactobacillus sakei and Lactococcus garvieae. All of them have at least one gene encoding known bacteriocins. The most active strains, Lc. casei 116 and Ll. sakei 205, provoked reductions higher than 2 log cycles of L. monocytogenes levels in food models, respectively. The selected LAB strains may be utilized to control L. monocytogenes throughout the ripening process in ripened soft cheeses and dry-cured fermented sausages. The combination of 16S rRNA sequencing with PFGE analysis with restriction Sgs I and Not I enzymes could be useful to control the implantation of these selected strains throughout the ripening process. Graphical abstract: Image 1 Highlights: 371 lactic acid bacteria were isolated from traditional ripened sausages and cheeses. The procedure followed allows to select 6 LAB active strains against L. monocytogenes. Lc. casei 116 and Ll. sakei 205 reduced 2 log of this pathogen in foods. The optimized PFGE analysis allows to control implantation of selected LAB during ripening.